Evaluation of Laccase Activities by Three Newly Isolated Fungal Species in Submerged Fermentation With Single or Mixed Lignocellulosic Wastes - Han, Mei-Ling; Yang, Jing; Liu, Ze-Yang; Wang, Chun-Rui; Chen, Si-Yu; Han, Ning; Hao, Wen-Yao; An, Qi; Dai, Yu-Cheng (Frontiers in Microbiology, 2021)
Three newly isolated fungal species, namely, Cerrena unicolor Han 849, Lenzites betulina Han 851, and Schizophyllum commune Han 881, isolated from their native habitats in Wulingshan National Nature Reserve of Hebei Province of northern China, were screened for laccase production with single or mixed lignocellulosic wastes. C. unicolor Han 849 was found to express the highest levels of laccase with single or mixed lignocellulosic wastes compared with L. betulina Han 851 and S. commune Han 881. The highest laccase activity from the mixed fungal culture of C. unicolor Han 849 and S. commune Han 881 or L. betulina Han 851 on Firmiana platanifolia was 1,373.12 ± 55.93 and 1,144.85 ± 34.97 U/L, respectively, higher than that from other tested conditions. L. betulina Han 851 or S. commune Han 881 mixed with other species was also helpful for accelerating laccase secretion due to reach maximum enzyme activity quickly. The treatment of mixing different species, including the mixture of two or three species, was obviously conducive to the improvement of laccase activity on Firmiana platanifolia. These results revealed that the fungal co-culture and the mixed lignocellulosic wastes contribute to the improvement of laccase activities and enhance laccase activities within a short period. These findings would be helpful for providing a new method for rapid production of low-cost laccase and for optimization of integrated industrial laccase production.